A Smooth Muscle Cell-Based Ferroptosis Model to Evaluate Iron-Chelating Molecules for Cardiovascular Disease Treatment - Sarah El Hajj; Laetitia Canabady-Rochelle; Isabelle Fries-Raeth; Caroline Gaucher (Current Issues in Molecular Biology, 2024)
Dysregulation of iron homeostasis causes iron-mediated cell death, recently described as ferroptosis. Ferroptosis is reported in many chronic diseases, such as hepatic cancer, renal, and cardiovascular diseases (heart failure, atherosclerosis). However, there is a notable scarcity of research studies in the existing literature that explore treatments capable of preventing ferroptosis. Additionally, as far as the author is aware, there is currently no established model for studying ferroptosis within cardiovascular cells, which would be essential for assessing metal-chelating molecules with the potential ability to inhibit ferroptosis and their application in the treatment of cardiovascular diseases. In this study, a smooth muscle cell-based ferroptosis model is developed upon the inhibition of the system Xc− transporter by erastin associated or not with Fe(III) overload, and its rescue upon the introduction of well-known iron chelators, deferoxamine and deferiprone. We showed that erastin alone decreased the intracellular concentration of glutathione (GSH) without affecting peroxidized lipid concentrations. Erastin with ferric citrate was able to decrease intracellular GSH and induce lipid peroxidation after overnight incubation. Only deferiprone was able to rescue the cells from ferroptosis by decreasing lipid peroxidation via iron ion chelation in a 3:1 molar ratio.